2022
DOI: 10.3389/fmolb.2022.857320
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of circRNA Biomarker for Gastric Cancer through Integrated Analysis

Abstract: Gastric cancer (GC) is one of the most common malignant tumors and ranks third in cancer mortality globally. Although, a lot of advancements have been made in diagnosis and treatment of gastric cancer, there is still lack of ideal biomarker for the diagnosis and treatment of gastric cancer. Due to the poor prognosis, the survival rate is not improved much. Circular RNAs (circRNAs) are single-stranded RNAs with a covalently closed loop structure that don’t have the 5′-3′ polarity and a 3′ polyA tail. Because of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 47 publications
(53 reference statements)
0
7
0
Order By: Relevance
“…To investigate potential dysregulated circRNAs in GC, high-throughput circRNA sequencing with ribosomal RNA depletion was conducted using five paired GC and non-tumoral tissues [ 24 , 37 ]. A total of 478 dysregulated circRNAs (fold change ≥2, P < 0.05) were identified, suggesting that these circRNAs may participate in GC development (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate potential dysregulated circRNAs in GC, high-throughput circRNA sequencing with ribosomal RNA depletion was conducted using five paired GC and non-tumoral tissues [ 24 , 37 ]. A total of 478 dysregulated circRNAs (fold change ≥2, P < 0.05) were identified, suggesting that these circRNAs may participate in GC development (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…PTX increased circRNA_0044556 expression in MDA-MB-231 cells, suggesting that circRNA_0044556 may be related to paclitaxel resistance. As a circRNA encoded by COL1A1, previous studies have shown that circRNA_0044556 plays a vital role in the occurrence and development of tumors, including colorectal cancer [20,21], gastric cancer [22] and TNBC [12]. The in nite malignant proliferation of tumor cells and inhibition of apoptosis are the core factors in tumor development and change [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, one circRNA can adsorb several miRNAs, one miRNA molecule can target a wide range of different mRNAs with the involvement of corresponding protein products in the development of several pathologies, and individual circRNAs can be markers of several diseases simultaneously. Many circRNAs, in particular circMTO1, circHIPK3, сirc_0001946, circPTPRA, and circCOL1A1, are potential targets for therapy or biomarkers of CAD ( Table 1 and Table 2 ), and play critical roles in cancer progression as well [ 175 , 176 , 177 , 178 , 179 ]. Additional comprehensive studies of the action mechanisms of individual circRNAs and the involved regulatory networks are needed.…”
Section: Circrnas Are Promising Biomarkers and Therapeutic Targets Fo...mentioning
confidence: 99%